Algebra-Grundlagen-Logarithmen



Beispiel Nr: 01
$c=\log_{b} a \Leftrightarrow b^{c}=a \\ \log_c a+\log_c b = \log_c (a \cdot b) \\ \log_c a-\log_c b =\log _c\frac{a}{b} \\ log_c a^n=n\log_c a \\ \\ \textbf{Gegeben:} \\ {a=2 \qquad b=2 \qquad c=2 \qquad n=2}\\ \\ \textbf{Rechnung:} \\ \log_{2} 2 =1 \Leftrightarrow 2^{1}=2 \\ \log_{2} 2+\log_{2}2 = \log_{2}(2 \cdot 2)= \log_{2}(2 \cdot 2)=2 \\ \log_{2} 2-\log_{2}2 =\log_{2}\frac{2}{2}= 0\\ \log_{2}2^2=2\log_{2}2 = 2\\ \log_{2} 2=\dfrac{\log_{2}2}{\log_{2}2}=1 $